AMO and happiness-at-work: a cross-generational analysis - Siew, Wei Soon (2018)
Malaysian companies are often faced with the difficulties of attracting new talents and retaining their employees. Training new employees is a costly and time consuming process. In order to increase staff retention rates, companies are including HRM strategies to take care of the employees’ well-being and keep them happy.